The dangers of fast food: understanding the perception of UiTM KBM Art & Design students towards fast food / Imran Abdullah Sharin - Abdullah Sharin, Imran (2014)
Fast foods are characterized as quick, easily accessible and cheap alternatives to home-cooked meals, designed for ready availability, use, or consumption and with little consideration given to quality or significance, according to the National Institutes of Health (NIH). They also tend to be high in saturated fat, sugar, salt and calories. In Malaysia, most students resort to fast food because they are constantly on the go, which often leaves little time for them to shop for and prepare meals in the same way as their parents or grandparents might have done. The fast food establishments, which offer drive-through service, answers a need for today's often over scheduled society. However, they are not fully aware of what fast food would do to their health. Despite its convenience and low cost, fast food contributes to heart disease, numerous types of cancer, diabetes and other chronic diseases, according to Dr. Steven Aldana, author of "The Stop and Go Fast Food Nutrition Guide" and former lifestyle medicine professor at Brigham Young University. High-calorie fast foods include too much saturated fat, trans fat and sodium, all of which negatively affect your cardiovascular system and overall health. This study aims to find out the perception of students of UITM KBM Art & Design on fast food. A questionnaire was used to collect relevant data and 50 responses were analyzed. The preliminary results show that students of UITM KBM Art & Design students perceive fast food to be bad for their health but only a handful agree that it is truly dangerous. Following an in-depth analysis, some recommendations for the study are presented.